Diversity and Inclusion in Japan: Issues in Business and Higher Education - Lailani Alcantara; Yoshiki Shinohara (Routledge, 2023)
Alcantara, Shinohara, and their contributors evaluate the current state of diversity and inclusion (D&I) within business and higher education in Japan, and the importance of D&I to the growth of Japan's economy and the enrichment of its society. Japan is widely understood to be a homogenous and patriarchal society, and while this is changing and was never wholly accurate, it certainly faces challenges in becoming more diverse and inclusive, particularly in its business and higher educational cultures. Grounded in research and offering best practices, the chapters in this book analyze critical issues relating to D&I in Japan at the individual, organizational, and industry levels. They present both a longitudinal analysis of the evolution and performance outcomes of D&I policies in Japanese corporations across industries, and rich studies of different underrepresented groups in Japan. These groups include immigrants, women, and people with disabilities. The contributors prescribe policies for promoting D&I in higher education, within businesses and at the governmental level. This book is an essential contribution to D&I discourse in the Japanese context that will be of great value to scholars of Japanese society and business, and an important extended case study for those looking at D&I more widely.
Keywords: 330; Accessibility; Aging Population; Corporate Social Responsibility; Disabilities; Reasonable Accommodation; Women Leaders